Secreted phospholipases A2 induce the expression of chemokines in microvascular endothelium - Beck, Grietje; Yard, Benito A.; Schulte, Jutta; Haak, Markus; Ackern, Klaus van; Woude, Fokko J. van der; Kaszkin, Marietta (Biochemical and biophysical research communications, 2003)
Acute respiratory distress syndrome (ARDS) is characterized by alterations in microvascular permeability. In ARDS secreted phospholipase A2 (sPLA2) IB and IIA are found to be highly upregulated. In this study, we therefore investigated the influence of exogenously added sPLA2-IB and sPLA2-IIA on the production of chemokines and adhesion molecules in lung microvascular endothelial cells (LMVEC). Treatment of LMVEC with sPLA2s resulted in a significant increase in the production of chemokines and adhesion molecules due to an increased expression of their mRNA and in an enhanced release of oleic acid. The upregulation of chemokines and adhesion molecules by LPS was stronger in the presence of sPLA2. Activation of NF-κB occurred upon stimulation with sPLA2. Moreover the MAPkinase pERK seems to be involved since a specific pERK inhibitor, e.g., U0126, but not a p38Kinase inhibitor, e.g., SB203580 prevented sPLA2-induced chemokine upregulation. Our data therefore suggest that LMVEC are a highly sensitive target for the direct action of extracellular sPLA2s.
Gesehen am 14.06.2022